Differences in the moderating role of supervisors’ and subordinates’ cognition on distributive justice in the relationship between psychological contract and organizational identification - Shen, Yan (Frontiers in Psychology, 2022)
The predictive role of psychological contract on organizational identification and the moderating role of supervisors' and subordinates' cognition on distributive justice in it were investigated. A sample of 133 supervisors and 437 direct subordinates collected from private service-based SMEs were analyzed by structural equation modeling, and the results showed that (1) relational psychological contract had a positive predictive effect on organizational identification and transactional psychological contract had a negative predictive effect on organizational identification; (2) subordinates' cognition on distributive justice played a moderating role in the prediction of psychological contract on organizational identification, and supervisor's cognition on distributive justice on subordinate's psychological contract and organizational identification did not reach a significant level. This indicates that there was a significant difference between supervisors' and subordinates' cognition on distributive justice.